Foreign ownership and intra-firm union density in Germany - Uwe Jirjahn (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2017)
From a theoretical viewpoint the relationship between foreign ownership and unionization is ambiguous. On the one hand, foreign owners have better opportunities to undermine workers' unionization. On the other hand, workers of foreign-owned firms have an increased demand for the protection provided by unions. Which of the two opposing influences dominates can vary according to moderating circumsta nces. This study shows that firm size and industry-level bargaining play a moderating role. The relationship between foreign ownership and unionization is negative in larger firms whereas it is positive in smaller firms. Coverage by industry-level collective bargaining makes a positive relationship both stronger and more likely.
Keywords: F23; F66; J51; J52; 330; Corporate Globalization; Foreign Direct Investment; Union Membership; Firm Size; Centralized Collective Bargaining